The CAP in the 2021-2027 MFF Negotiations - Alan Matthews (Intereconomics, 2018)
Pressure to embed environmental and climate action even more centrally into the CAP has also moved up the political agenda because of the EU's commitment to action on the Paris Climate Agreement and the UN Sustainable Development Goals (SDGs).
Keywords: 330